P1136STUDY DESIGN OF ELIXIR, A MULTICENTER EUROPEAN PHASE III CLINICAL TRIAL AIMED TO TEST A GLUCOSE-SPARING PD SOLUTION WHERE GLUCOSE IS MOSTLY REPLACED WITH OSMO-METABOLIC AGENTS. (6th June 2020) - Kleophas, Werner; Bonomini, Mario; Divino, Jose Carolino; Reboldi, Gianpaolo; Iacobelli, Massimo; Arduini, Arduino
Abstract: Background and Aims: Peritoneal dialysis (PD) faces particular challenges that include multiple barriers to the therapy and unsatisfactory and poorly defined technique survival as well as limitations relating to peritoneal membrane longevity and metabolic alterations. Glucose is the most used osmotic agent for PD. However, the peritoneal membrane is not impermeable to glucose, so that a rapid reduction of the osmotic gradient and an increase of serum carbohydrates are seen in CAPD patients. Increased glucose absorption may result in metabolic abnormalities like hyperglycemia, hyperinsulinemia, obesity and hyperlipidemia. Therefore, a more satisfactory composition of PD solution (PDS) is urgently needed. XyloCore PDS (Iperboreal Pharma, Pescara, Italy) has been formulated to significantly reduce glucose exposure by replacing most of it with two crystalloid agents, D-xylitol and L-carnitine. A randomized controlled trial to evaluate the safety and efficacy of a newly introduced PDS is needed to provide the necessary clinical evidence to guide policy decision-making. The randomized controlled study designs in small populations are challenging because it is very difficult to adequately assess changes between variable groups. The aim of this program was to develop an adequate clinical trial protocol and validate it by reaching agreement with regulatory authorities. Method: Pre-approval trials include a study protocol and test the drug in a highly selected patient population designed to provide the most robust evidence on the drug's benefits and risks. The scientific integrity of the trial and the credibility of the data from the trial depend substantially on the trial design, including the primary and secondary endpoints, minimization of bias (including randomization and blinding), "discontinuation criteria" for individual subjects, statistical analysis of primary end-point, and the strategy to handle missing data. An international steering committee of clinical experts and statistician has been set for this study to discuss and develop an adequate study protocol to produce evidence to support regulatory submissions. The proposed protocol has been discussed with the regulatory agency in Germany BfArM in order to reach agreement on the study design for this Phase 3 pre-approval trial. Results: BfArM agreed with the proposed study design for the planned pivotal phase III study NCT03994471.The study will be a randomized, controlled parallel groups, open, multicenter study, comparing the effects of the low glucose PD solution, XyloCore, to glucose regimen only, in ESRD patients receiving CAPD. All patients will receive 7.5% Icodextrin for nocturnal (long-dwell) exchange. Randomization will be performed centrally and the study will be stratified for diabetic/non-diabetic patients. The primary objective is to demonstrate the non-inferiority of XyloCore compared to the glucose PDS with regards to safety and efficacy. The primary outcome measure is total weekly Kt/V urea after a 24-week period using the assigned PD solution, assessed using a peritoneal function test. The non-inferiority margin of -0.25 with a 1-sided level of significance of 2.5% and 80% power has been agreed (Kt/V will not be less than 1.7 at any time). Consequently, a sample size of 170 patients has been defined. The Agency agreed that the study cannot be blinded and recommended a blinded and independent assessment of the end-point Kt/V urea. A Feasibility Study is in progress to identify the centers in several countries. Conclusion: A well written and complete protocol is essential for a high-quality study. Many clinical studies have problems with incompleteness, ambiguity and inconsistency. Many of these problems are avoidable by careful planning during the protocol writing process. Involving regulatory authorities early in the discussion of the protocol should ensure acceptability of study design of pre-approval clinical trials.